Keterkaitan Hubungan Parameter Kualitas Air Pada Budidaya Intensif Udang Putih (Litopenaeus vannamei) - Heri Ariadi; Abdul Wafi; Muhammad Musa; Supriatna Supriatna (Faculty of Science and Technology University Ibrahimy, 2021)
Water quality parameters play an important role in intensive pond ecosystems. The purpose of this study was to determine the relationship between of water quality parameters in intensive shrimp farming of L. vannamei. This research was carried out for 95 days of intensive shrimp farming in PT. Menjangan Mas Nusantara Company, Banten, with the physical, chemical, and microbiological parameters of water as the main reference object of observation. The results showed that during the shrimp culture period the pond water quality parameter concentration was considered to be quite optimal with a stable fluctuation trend, except for the salinity and TOM parameters whose values ​​were above the water quality standard. Correlation test results state that between the physical chemical parameters have a strong and heterogeneous relationship, with the strongest parameters of pH, phosphate, nitrite, and TOM. As for the microbiological variables, the correlation of physical chemistry parameters of water is considered to be very weak, because from the correlation test results, only DO parameters showed the correlation with microbiological parameters. The conclusion of this study, that during intensive shrimp culture period, the physical and chemical parameters of water have a strong correlation of association between one another and the highest are pH, phosphate, nitrite, and TOM, but only dissolved oxygen parameters that show the relationship correlation with microbiological parameters.